Itinéraires professionnels masculins et féminins en milieu bancaire: Le cas de la Banque d'Hochelaga, 1900-1929 - Dagenais, Michèle (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1989)
Abstract This article aims at retracing the process of feminization of office work in banks, looking at the case of female and male employees at the head office of the Banque d'Hochelaga between 1900 and 1920. First, we look at the consequences of the administrative revolution on the organization of work in the bank, especially at the sexual division of labour. While men are present in all occupation groups, women occupy a narrower range of occupations. A number of studies have concluded that women had no opportunity to occupy jobs that were not subordinate and badly paid, leaving more qualified positions to male workers. This type of conclusion, which presents the female workforce as homogeneous and masks the diversity of women's professional experience, raises many problems. A comparative analysis of individual itineraries within the bank, rather than the more conventional study centred on the organization of labour, reveals a diversity of experience and professional practices amongst the female as well as amongst the male bank employees.